2017
DOI: 10.1177/1010428317711951
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-193a-3p inhibits cell growth and migration in renal cell carcinoma by targeting PTEN

Abstract: Although miR-193a-3p has been found to be dysregulated in variety of human tumors, little is known about its role in renal cell carcinoma. This study was designed to investigate the function and underlying mechanism of miR-193a-3p in human renal cell carcinoma tissues and cell lines. Here, we demonstrated that the expression of miR-193-3p was increased in renal cell carcinoma tissues and cell lines. In addition, knockdown of miR-193a-3p significantly inhibited cell proliferation and colony formation and induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…In human osteosarcoma, miR-142-5p also suppresses proliferation and promotes apoptosis by targeting phospholipase A and acyltransferase 3 ( 19 ). In the present study, miR-142-5p was shown to promote proliferation and migration of ccRCC cells by targeting TFAP2B , which is consistent with study results reported by Liu et al ( 20 ) that revealed that miR-142-5p promotes cell growth and migration of ccRCCs by targeting BTG anti-proliferation factor 3. These results revealed the importance of the miR-142-5p in ccRCC development.…”
Section: Discussionsupporting
confidence: 93%
“…In human osteosarcoma, miR-142-5p also suppresses proliferation and promotes apoptosis by targeting phospholipase A and acyltransferase 3 ( 19 ). In the present study, miR-142-5p was shown to promote proliferation and migration of ccRCC cells by targeting TFAP2B , which is consistent with study results reported by Liu et al ( 20 ) that revealed that miR-142-5p promotes cell growth and migration of ccRCCs by targeting BTG anti-proliferation factor 3. These results revealed the importance of the miR-142-5p in ccRCC development.…”
Section: Discussionsupporting
confidence: 93%
“…Emerging evidences have shown that miRNAs play important roles in the development and progression of RCC [17][18][19][20][21]. These miRNAs can act as tumor suppressor genes or oncogenes by modulating the target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous targets of miR-193a-3p have been reported [26,28,32,33]. In this study, the TargetScan, miRNA.ORG, and miRDB software were used for the prediction of target genes.…”
Section: Discussionmentioning
confidence: 99%